2018
DOI: 10.23822/eurannaci.1764-1489.72
|View full text |Cite
|
Sign up to set email alerts
|

Impact of allergy on children with attention deficit hyperactivity disorder

Abstract: Background. Attention deficit hyperactivity disorder (ADHD) is commonly present worldwide, causing serious problems to those affected. ADHD was suggested to be secondary to allergic disorder or its medication. Both ADHD and allergy depend on complex environmental and genetic interaction, and they meet the hypersensitivity criteria. Objective. Detect the percentage of allergy in ADHD children, the common allergic disorders and allergens, and the effect of allergy on symptom and severity of ADHD. Material and me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
(14 reference statements)
0
6
0
Order By: Relevance
“…This finding contradicts current opinions raised by many researchers. A number of previous evidence has supported the association between ADHD and allergic/autoimmune diseases 10 , 11 , 27 . Various allergic diseases, like allergic rhinitis, atopic dermatitis, and asthma, have been associated with ADHD 16 19 .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…This finding contradicts current opinions raised by many researchers. A number of previous evidence has supported the association between ADHD and allergic/autoimmune diseases 10 , 11 , 27 . Various allergic diseases, like allergic rhinitis, atopic dermatitis, and asthma, have been associated with ADHD 16 19 .…”
Section: Discussionmentioning
confidence: 91%
“…Allergies are immune responses and usually involve chronic inflammation 9 . However, whether inflammation and irritation increase the risk of neuropsychological consequences in children with atopic diseases is still unclear 10 12 . For example, allergic rhinitis is associated with significantly impaired mental health and impaired cognitive function 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Symptoms of allergic rhinitis may lead to daytime inattention, irritability and hyperactivity, which is commonly observed in ADHD children. Although there have been studies showing that AR has a strong relationship with ADHD [8, 9], the mechanism is still controversial. The prevalence of ADHD and allergic disease has increased worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis by Miyazaki et al 10 demonstrated that children with ADHD are more likely than controls to have multiple types of allergic diseases. El-Hamid et al 15 concluded that children with ADHD experienced an increased prevalence of multiple types of allergic diseases. In particular, recent studies have reported relationships between ADHD and bronchial asthma, one of the typical allergic diseases in children.…”
Section: Discussionmentioning
confidence: 99%
“…demonstrated that children with ADHD are more likely than controls to have multiple types of allergic diseases. El‐Hamid et al 15 . concluded that children with ADHD experienced an increased prevalence of multiple types of allergic diseases.…”
Section: Discussionmentioning
confidence: 99%